Bahan Ajar Elektronik Book Berbasis Kvisoft Flipbook Maker pada Mata Kuliah Penilaian Program PLS - Hayati, Nurul; Azizah, Zahratul (Universitas Negeri Semarang, 2021)
Each course has its own uniqueness and distinctiveness, therefore it is necessary to develop e-book teaching materials for these courses. It aims to adjust to the uniquenessand distinctiveness which ultimately leads to improving the quality of learning. Indeveloping e-book teaching materials, apart from being based on materials andcurriculum, it is also necessary to analyze student needs so that the e-book teachingmaterials are right on target. The purpose of this study was to analyze the importance ofkvisoft flipbook maker-based teaching materials in the PLS program assessment course.The research method used is a survey method. Data collection was carried out using anopen questionnaire made through google form and addressed to fifth semester studentswho took PLS program assessment courses. In addition, researchers also madeobservations in the learning process. The data obtained are quantitative data andqualitative data. Quantitative data were analyzed using the percentage formula, whilequalitative data were analyzed descriptively. The data analysis of the importance of thekvisoft flipbook maker-based e-book is part of the development research (R & D) on thedevelopment of teaching materials for the PLS program evaluation e-book, in which thise-book product can be used by students in learning. Based on the results of the analysis ofthe importance of this ebook based on kvisoft flipbook maker, it is obtained that thisebook needs to be developed to make it easier for students to understand the material well.